The Impact of Firm Size, Capital Structure and Dividend Policy on Firm Value during Covid-19 Pandemic : Dampak Ukuran Perusahaan, Struktur Modal dan Kebijakan Dividen Terhadap Nilai Perusahaan - Purnamasari, Dian Indri; Fauziah, Muthia Riza (Journal of Accounting Science, 2022)
The present study aims to obtain empirical evidence for the impact of firm size, capital structure and dividend policy on the firm value of hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange (IDX) for the years 2019-2020. The data used in this research are secondary data obtained from companies’ annual reports. The study population comprised of hotel, restaurant, and tourism companies listed on IDX for the years 2019-2020. The sample consists of 24 hotel, restaurant, and tourism companies listed on IDX for the years 2019-2020 and selected using a purposive sampling technique. The study used a multiple linear regression analysis. The results suggested that firm size, capital structure, and dividend policy have no impact on the firm value of hotel, restaurant, and tourism companies listed on IDX for the years 2019-2020.